Online Reading Strategy in Academic Reading by Foreign Language Learners during Covid 19 Outbreak - Erni Erni (STAI Hubbulwathan Duri, 2021)
This mixed-method research used questionnaires, in-depth interviews, and open-ended questions as the instrument of data collection. Twenty-five samples were selected randomly from 112 populations. The objectives of the study were to explore online reading strategies in academic reading by foreign language learners during the Covid 19 outbreak. This study revealed that: Using online reading strategies by foreign language learners were varied in four different types, namely global strategy, problem-solving strategy, support strategy, and soci0-effective strategy. Motivation influenced foreign language learners' online reading strategies for 13.65% in academic reading during the Covid 19 outbreak; meanwhile, age and gender influenced less. Motivation influenced online reading strategies used by foreign language learners during the Covid 19 outbreak for two purposes: integrated and instrumental motivations. These two types of motivation influenced the choices and use of learners' online reading strategies during the Covid 19 outbreak.